ANALISIS KESALAHAAN EJAAN TERHADAP TEKS BERITA “BIKIN GAGAL GINJAL, ETILEN GLIKOL DI OBAT SIRUP TERNYATA ‘FAMILIAR’ DI MESIN” PADA MEDIA ONLINE DETIKOTO” - Reva Yulianizar; Siti Zulfa Waliah (Universitas Maritim AMNI Semarang, 2022)
In online media, writing errors regarding language are often found. One of them is online media in the process of writing news texts sometimes in a hurry because it is based on a predetermined deadline. This error occurs because it violates two of the three terms of word selection, namely